Mechanism of Abelmoschus manihot L. in the Treatment of Contrast-Induced Nephropathy on the Basis of Network Pharmacology Analysis - Xu, Zhongchi; Qian, Lichao; Niu, Ruge; Wang, Yibei; Yang, Ying; Liu, Chunling; Lin, Xin (Frontiers in Nephrology, 2022)
Background: Contrast-induced nephropathy (CIN) is increasingly seen in patients receiving contrast medium. Abelmoschus manihot (L.) Medik. (Malvaceae) and its preparations are widely used and effective in the treatment of various chronic kidney diseases and CIN in China. It is supposed to be an important adjuvant therapy for CIN. Methods: PubMed and CNKI were searched for the main compounds of A. manihot L.. The Swiss target prediction platform, OMIM, GeneCards, DisGeNET and DrugBank databases were mined for information relevant to the prediction of targets that A. manihot L. in the treatment of CIN. Subsequently, STRING database was applied for the construction of PPI protein interaction network, meanwhile the core targets were screened. Metascape database was uesd to performed the GO function and kegg signal pathway enrichment analysis. AutoDockTools and PYMOAL were used for molecular docking. Vitro experiments were used to verify the effect of TFA, the main active component of A. manihot L., in the intervention of iopromide-induced cells injury. Results: A total of 17 chemical components and 133 potential targets in A. manihot L. were obtained. The top 15 proteins with higher degree value were selected from PPI network model, AKT1, PIK3R1, EGFR, SRC,AR, APP, TNF, GAPDH, MMP9, PTPN1 , etc. may be core targets. The enrichment analysis indicated that A. manihot L. was involved in the regulation of PI3K/AKT signaling pathway, FoxO signaling pathway, VEGF signaling pathway, HIF-1, TNF signaling pathway, melanoma, hepatitis B and other signaling pathways which was mainly associated with regulation of transcription and apoptosis, protein phosphorylation, inflammatory response, aging, and cell proliferation. Molecular docking indicated that the key components and core targets had a good binding ability. The vitro experiments illustrated that TFA reduces iopromide induced renal tubular cell injury and apoptosis which may be related to regulating the phosphorylation of AKT. Conclusion: The study preliminarily revealed the multi-component, multi-target and multi-pathway synergistic effect of A. manihot L. on CIN, which provided theoretical reference and basis for the study of pharmacological mechanism of A. manihot L. in the treatment of CIN. Keywords: Contrast-induced nephropathy, Abelmoschus manihot L., Network Pharmacology, Molecular Docking, Total flavonoids.